The concept of lichen refugia classification. A proposal based on the case study of Krajeńskie Lakeland, Poland - Gruszka, Wojciech (Ecological Questions, 2017)
The article presents a proposal for the classification of lichen refuges based on the research conducted in the Krajeńskie Lakeland in 2009-2014. Four types of refuges have been distinguished during the research: 1 - primeval (natural) - associated with the least transformed areas, 2 – regenerative (semi-natural) – with species of high conservation value, spread by natural forces despite a small anthropogenic impact, 3 – colonized (anthropogenic) – solely formed by human activity and extraneously inhabited by adventive lichens, 4 – incidental (spontaneous) – formed instantaneously as a result of a favourable situation or an event. The last type was not found in the course of the study. The publication presents the characteristics of all types of refuges along with a key for their identification.